Diversity Index of Insect Species on Sorghum Plantations in Kolam Village, Percut Sei Tuan District, Deli Serdang - Tarihoran, Parlindungan; Siregar, Ameilia Zuliyanti; Marheni (Indonesian Journal of Agricultural Research, 2020)
This research aimed to know the diversity of insects of sorghum plantations and the status of insect functions in sorghum plants. The purposive sampling method were done, which used 4 traps, consist of yellow sticky trap, sweep net, pitfall trap and light trap for 8 observations research were done from May to September 2019 at Kolam Village, Percut Sei Tuan District of Deli Serdang Regency, then continue to identified in Pest Laboratory Faculty of Agriculture University of Sumatera Utara, Medan. The results showed that there were 117 individuals insects which consist of 10 orders and 33 families. The highest relative density was 14.74% and the lowest was 0.42% sere recorded, while the highest relative frequency was 4.08% and the lowest was 1.53%. The value of insect diversity index was 3.115 (High), it is mean the diversities of insects varied and the habitat was good for growth of insects. The value of evenness index was 0.891 (high) and richness index was 4.15 (high). The dominant insects recorded from Order of Hymenoptera (Family of Formicidae), continued to Coleoptera (Family of Scarabaeidae; Coccinellidae) are quite diverse in the sorghum plantations. The function status of insects was recorded as herbivores, parasitoids, predators, pollinators and decomposer were determined.